PENGARUH MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING TERHADAP NUMERASI KELAS V DI SDN PUJER BARU 2 - Ajeng Nuraini Wulandari (Jurnal Eduakasi dan Penelitian Tindakan Kelas, 2023)
The ability of students in solving mathematical problems at SDN PUJER NEW 2is indeed low. This is due to the lack of understanding and understanding inunderstanding the questions given, as well as the lack of motivation of studentsin participating in learning. In addition, another factor is in terms of educatorswho are still lacking in mastering learning models to be applied when teaching.The importance of the learning model will greatly affect the understanding ofstudents in understanding the material taught by educators. This study aims todetermine the understanding of students in solving mathematical problemsusing creative problem solving learning models. The problem to be solved isrelated to flat shapes to find out sides, angles, diagonals, space diagonals, planediagonals, edges and so on. In this study, using cardboard box media as asupport for students in solving problems creatively and attracting students'curiosity in making flat shapes from cardboard box. In accordance with thelearning model used, students must be creative in solving mathematicalproblems. This research is a qualitative research using a sampling technique bytaking ten students from the total number of class V. Students will be givenseveral math problems which later the results of the research will show howmuch influence the creative problem solving learning model with cardboardbox media has in its completion